(untitled) (Research, Society and Development, 2020)
This study aimed to problematize hemophilia in the context of School Physical Education classes, so that possible interventions and pedagogical practices are situated. Hemophilia is a genetic and hereditary disease that causes difficult blood clotting. The school environment, in the current structure, has sought to serve a student diversity. In this locus, integrality actions are problematized. Hemophiliacs, due to their genetic conditions, face numerous difficulties daily, whether in adhering to treatments, the stigmatizations attributed by the eyes of the other and the exclusion itself in the social and school scope, especially in physical education classes. For this, the Brazilian academic production on the themes Hemophilia, Physical Education, Interventions and Pedagogical Practices was used. The search for this literature was carried out in three web databases: the Brazilian Digital Library of Theses and Dissertations (BDTD), the Scientific Eletronic Library Online (SCIELO) and academic Google. It is concluded that the adoption of methodological didactic strategies in school physical education classes, allows the participation of hemophiliac students, without any exclusion processes, thus making them also protagonists in the teaching and learning processes.